2016
DOI: 10.1039/c5ra23222h
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt oxide nanoparticle embedded N-CNTs: lithium ion battery applications

Abstract: ZIF-12 is converted to Co/N-CNTs at 950 °C under an argon atmosphere. The obtained hybrid nanocomposite is used for LIBs application as an anode material with superior charge storage performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 62 publications
1
38
0
1
Order By: Relevance
“…Guo et al studied the electrochemical properties of Co 3 O 4 /graphite composites and showed that the reversible capacity increased with decrease in graphite content and increase in the calcination temperature, while cycling stability decreased dramatically with decrease in graphitic content [47]. Khan et al reported on the excellent performance of cobalt oxide nanoparticles embedded in nitrogen-doped carbon nanotubes, which is attributed to the nitrogen doping of carbon nanotubes, the strong interaction between the encapsulated cobalt oxide nanoparticles with the carbon nanotubes, the porosity and the specific surface area of the nanomaterial [52]. In addition, Qiu et al investigated the electrochemical performance of carbon-coated Co 3 O 4 nanoparticles in comparison to bare Co 3 O 4 electrode and concluded that the superior electrode performance of the first was attributed to better dispersion and to the thin carbon shell coating of the nanoparticles on the electrode surface [54].…”
Section: Applications Of Cobalt-based Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Guo et al studied the electrochemical properties of Co 3 O 4 /graphite composites and showed that the reversible capacity increased with decrease in graphite content and increase in the calcination temperature, while cycling stability decreased dramatically with decrease in graphitic content [47]. Khan et al reported on the excellent performance of cobalt oxide nanoparticles embedded in nitrogen-doped carbon nanotubes, which is attributed to the nitrogen doping of carbon nanotubes, the strong interaction between the encapsulated cobalt oxide nanoparticles with the carbon nanotubes, the porosity and the specific surface area of the nanomaterial [52]. In addition, Qiu et al investigated the electrochemical performance of carbon-coated Co 3 O 4 nanoparticles in comparison to bare Co 3 O 4 electrode and concluded that the superior electrode performance of the first was attributed to better dispersion and to the thin carbon shell coating of the nanoparticles on the electrode surface [54].…”
Section: Applications Of Cobalt-based Nanoparticlesmentioning
confidence: 99%
“…Additionally, with increasing calcination temperature, the diffraction peaks for cobalt/ cobalt oxide became sharper in contrast to those for carbon, indicating that the crystallinity of cobalt-based nanoparticles increased and graphite content decreased due to its partial oxidation [47]. According to SEM and TEM micrographs, cobalt-based nanoparticles were spherical, coated with carbon and dispersed in the carbon matrix [54], uniformly distributed on carbon layered structures with particle size of 5-30 nm [53], supported on carbon with random size distribution in the range from 1 to 32 nm [50], embedded in carbon with average particle size of 8-10 nm [51] and encapsulated within carbon nanotubes with an average particle size of 50 nm [52]. N 2 adsorption-desorption isotherms of the as-synthesized nanocomposites exhibited the type IV isotherm with a H3-type hysteresis loop, demonstrating the mesoporous nature of the materials, while the textural properties of the materials varied widely (S BET = 76-365 m and the average pore size varied from 4.8 to 6.9 nm depending on the calcination temperature [51].…”
Section: Structure and Characterization Of Supported Cobalt Oxide Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…CoO/N-CNTs 1250 83 1100 (50) 100 [16] Porous carbon spheres 1213 -506 (50) 100 [27] High concentration of Nitrogen doped-CNTs 730 68 494 (100) 100 [28] N-doped graphene/Fe-Fe 3 C nanocomposite 904 24.6 1098 (48) 100 [29] Co-doped ZnO coated with carbon 1663 -725 (50) 100 [30] Co CoO/N-CNTs 1250 83 1100 (50) 100 [16] Co 3 O 4 /TiO 2 632.5 -602.8 (480) 200 [37] Doped hollow porous grapheme (DPHG) 2300 -900 (100) 100 [38] b-Co(OH) 2 /grapheme hybrid 944 97 640 (150) 100 [39] GC-Co(OH) 2 1146 -706 (50) 58 [40] NiO/GNS 1398 -982 (50) 100 [41] Co(OH) 2 /Co 3 O 4 hybrid 1452 73.42 1160 (40) 58 [42] Quadrate tubular Co 3 O 4 nanoboxes 1447 -1240 (50) 200 [43] ZnO@C/CNT 1551 -758 (100) 100 [44] CNT@Co 3 O 4 850 --- [45] Co 3 O 4 nanobelts 1400 -980 (60) 100 [46] CoO nanoporous array on…”
Section: Discussionmentioning
confidence: 99%
“…The cobalt oxide/NCNT composite material showed an excellent lithium charge/discharge and storage, retaining 95% capacity after 50 cycles and a reversible capacity of ca.1100 mA h g -1 . [16] We have selected a number of porous and non-porous cobalt based MOFs from the literature and carbonized at various temperatures ranging from 600 °C to 900 °C. In current work, we obtained Co-oxide/carbon composite which on testing reveals high performance activity as an anode material for LIBs.…”
Section: Comparison Of Barementioning
confidence: 99%